2018
DOI: 10.1155/2018/3678795
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition of Solanum retroflexum Analysed with the Aid of Ultra-Performance Liquid Chromatography Hyphenated to Quadrupole-Time-of-Flight Mass Spectrometry (UPLC-qTOF-MS)

Abstract: Solanum retroflexum (nightshade) is an edible plant that is consumed in some regions of South Africa. Its leaves are a good source of vitamins, proteins, and minerals. It appears that there is no scientific report about the phytochemical composition of S. retroflexum. Here, ultra-performance liquid chromatography coupled to quadruple-time-of-flight mass spectrometry (UPLC-qTOF-MS) technique was use to achieve an untargeted metabolite fingerprinting of this plant. A total of 30 phytochemicals, including alkaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…1a and b were observed and indicated isomers of CQA. Daji et al [14] reported a similar observation when methanol extracts were screened on the UPLC-qTOF-MS. A precursor ion at m/z 295 with a retention time of 4.32 min was observed for all the kosmotropes and chaotropes except for AgNO 3 , KNO 3 and Na 2 CO 3 . Interestingly, the precursor ion at m/z 295 and 4.32 min was not reported by Daji et al [14] in the methanol extracts they analyzed on the UPLC-qTOF-MS, probably indicating that this was a unique compound.…”
Section: Lc-ms Analysis Of Metabolites Obtained From Leaves Of S Retroflexum Using Ethanol Extracts From the Atpe System Lc-ms Analysis Omentioning
confidence: 63%
See 3 more Smart Citations
“…1a and b were observed and indicated isomers of CQA. Daji et al [14] reported a similar observation when methanol extracts were screened on the UPLC-qTOF-MS. A precursor ion at m/z 295 with a retention time of 4.32 min was observed for all the kosmotropes and chaotropes except for AgNO 3 , KNO 3 and Na 2 CO 3 . Interestingly, the precursor ion at m/z 295 and 4.32 min was not reported by Daji et al [14] in the methanol extracts they analyzed on the UPLC-qTOF-MS, probably indicating that this was a unique compound.…”
Section: Lc-ms Analysis Of Metabolites Obtained From Leaves Of S Retroflexum Using Ethanol Extracts From the Atpe System Lc-ms Analysis Omentioning
confidence: 63%
“…1a and b). Similarly, Daji et al [14], Ramabulana et al [27] and Pinela et al [32] reported on precursor ions at m/z 609 and m/z 593 as flavonoids.…”
Section: Lc-ms Analysis Of Flavonoidsmentioning
confidence: 87%
See 2 more Smart Citations
“…A total of 20 experimental runs were Most of the flavonoids contained either kaempferol, apigenin or isohamnetin core moieties. These illustrate that sugar moieties mostly attached to the basic skeleton flavonoid of DPSE and the total number of sugar moieties and their attachment to the structure of flavonoid effect their antioxidant activity [63]. In addition to the above, phenolic acid metabolites such as sinapic acid and E-p-coumatic acid have been detected in DPSE.…”
Section: Experimental Designmentioning
confidence: 79%